Travel Medicine Curricula across Canadian Pharmacy Programs and Alignment with Scope of Practice - Heidi V.J. Fernandes; Brittany Cook; Sherilyn K.D. Houle (MDPI AG, 2020)
Limited research exists on pharmacy students' training in travel medicine, and how this aligns with scope of practice. This research aimed to detail travel medicine education across pharmacy programs in Canada and map this against the scope of practice for pharmacists in each university's jurisdiction. A survey based on the International Society of Travel Medicine's Body of Knowledge was developed and distributed to all Canadian undergraduate pharmacy schools to identify topic areas taught, teaching modalities utilized, and knowledge assessment performed. Educational data was collected and analyzed descriptively, and compared to pharmacists' scope of practice in the province in which each university is located. Training provided to students varied significantly across universities and topic areas, with topics amenable to self-care (e.g., traveller's diarrhea and insect bite prevention) or also encountered outside of the travel context (e.g., sexually transmitted infections) taught more regularly than travel-specific topics (e.g., dengue and altitude illness). No apparent relationship was observed between a program's curriculum and their provincial scope of practice. For example, training in vaccine-preventable diseases did not necessarily align with scope related to vaccine administration. Alignment of education to current and future scope will best equip new practitioners to provide care to travelling patients.